Botanical Concepts Understanding of Biology Education Students - Khusnul Khotimah; Mucharommah Sartika Ami; Fatikhatun Nikmatus Sholihah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to identify the botanical concepts understanding of biology education students at Universitas KH. A. Wahab Hasbullah. 36 sample students were given a test with two tiers questions (multiple choice with confidence level). The students involved were students who had taken a botany courses. Test results were analyzed descriptive qualitatively. The findings revealed that there were 36,1% of students who understood the concept; 36,1% of students experienced misconception; and 27,8% of students did not understand the concept. Keywords: Botanical concept; Biology education student; Concept understanding.